Immunization with plant-based vaccine expressing Toxoplasma gondii SAG1 fused to plant HSP90 elicits protective immune response in lambs - Campero, Lucia Maria; Gual, Ignacio; Sander, Valeria; Mendoza Morales, Luisa; Ramos Duarte, Victor; Formigo, Paula; Sosa, Emiliano; Lázaro, Fermín; Scioli, Maria Valeria; Atela, Agustín; Legarralde, Ariel; Hozbor, Federico Andres; et al. (Elsevier, 2025)
Toxoplasma gondii is a protozoan parasite causing toxoplasmosis, a principal concern for public health and livestock industries. Effective vaccination strategies are crucial for controlling toxoplasmosis, particularly in the lamb, which are significant reservoirs of T. gondii. In addition, ovine toxoplasmosis also causes economic losses due to abortions and reproductive complications. In this study, we evaluated two immunization strategies to elucidate the immune protective potential of T. gondi major surface protein SAG1 fused to the plant heat shock proteins 90-kDa (pHsp90) adjuvant against experimental toxoplasmosis in lambs. We performed an oral administration of fresh leaves homogenate infiltrated with a B- and T-cell antigenic epitope-containing surface protein SAG1 (SAG1HC) fused to Arabidopsis thaliana Hsp90 (AtHsp81.2-SAG1HC) (Plant Vaccine) and a subcutaneous administration of recombinant SAG1HC fused to Nicotiana benthamiana Hsp90 (NbHsp90.3-SAG1HC) produced in Escherichia coli (Recombinant Vaccine). Our results showed that only the Recombinant Vaccine significantly increased anti-rSAG1 total IgG values (∼ 4-fold more than the Vehicle and Control groups). In addition, only lambs immunized with the Plant Vaccine showed a significant increase (∼ 3-fold more than the Vehicle and Control groups) in IFN-γ serum levels after the experimental infection (evaluated 8 days post-challenge). On the other hand, we also observed a statistically significant decrease (∼ 80 % less) in histopathological lesions (injury score) in challenged vaccinated lambs compared to challenged but not vaccinated animals (Vehicle and Control groups). Previously, we showed that the chimera recombinant Gra4-Gra7 protein is an acute marker of human infection. Since Gra4-Gra7 is not connected to the SAG1 immunogen, this chimera allows us to monitor infection in challenged lambs early. All lambs from the Control and Vehicle groups showed higher rates of serological reactivity than lambs from the vaccinated groups, concurrently with increased severity of lesions. These results suggest that the Plant-based and Recombinant Vaccines are promising candidates for controlling T. gondii infection in lambs, with potential benefits for enhancing public health and animal welfare.